Integrative species delimitation and biogeography of the Rhinella margaritifera species group (Amphibia, Anura, Bufonidae) suggest an intense diversification throughout Amazonia during the last 10 million years - Antoine Fouquet; Miqueias Ferrão; Miguel T. Rodrigues; Fernanda P. Werneck; Ivan Prates; Leandro J.C.L. Moraes; Tomas Hrbek; Juan C. Chaparro; Albertina P. Lima; Renata Perez; Andre Pansonato; Vinicius T. Carvalho; et al. (Systematics and Biodiversity, 2024)

Relicts in the mist: Two new frog families, genera and species highlight the role of Pantepui as a biodiversity museum throughout the Cenozoic - Antoine Fouquet; Philippe J.R. Kok; Renato Sousa Recoder; Ivan Prates; Agustin Camacho; Sergio Marques-Souza; José Mario Ghellere; Roy W. McDiarmid; Miguel Trefaut Rodrigues (Molecular Phylogenetics and Evolution, 2024)

Large‐scale DNA‐based survey of frogs in Amazonia suggests a vast underestimation of species richness and endemism - Jean‐Pierre Vacher; Jérôme Chave; Francesco Gentile Ficetola; Guilhem Sommeria‐Klein; Shengli Tao; Christophe Thébaud; Michel Blanc; Agustín Camacho; José Cassimiro; Timothy J. Colston; Maël Dewynter; Raffael Ernst; et al. (Journal of Biogeography, 2020)
Aim Mapping Amazonian biodiversity accurately is a major challenge for integrated conservation strategies and to study its origins. However, species boundaries and their respective distribution are notoriously inaccurate in this region. Here, we generated a georeferenced database of short mtDNA sequences from Amazonian frogs, revised the species richness and the delimitation of bioregions of the Eastern Guiana Shield and estimated endemism within these bioregions. Location Amazonia, with a focus on the Eastern Guiana Shield. Taxon studied Amphibia: Anura. Methods We used an extensive DNA‐based sampling of anuran amphibians of Amazonia using next‐generation sequencing to delimit Operational Taxonomic Units (OTU) and their distribution. We analysed this database to infer bioregions using Latent Dirichlet Allocation modelling. We then compared endemism within these bioregions based on our results and the current IUCN database, and inferred environmental variables that contributed the most to the biogeographic pattern. Results The recognized anuran species richness within the focal area increased from 440 species currently listed by the IUCN Red List to as much as 876 OTUs with our dataset. We recovered eight bioregions, among which three lie within the Eastern Guiana Shield. We estimated that up to 82% of the OTUs found in this area are endemic, a figure three times higher than the previous estimate (28%). Environmental features related to seasonal precipitations are identified as playing an important role in shaping Amazonian amphibian bioregions. Main conclusions Our results have major implications for defining future conservation priorities of this vast area given that endemism in most Amazonian bioregions is vastly underestimated, and might therefore hide a large portion of threatened species. Moreover, these findings raise concern about meta‐analyses based on public databases within Amazonia dealing with poorly known groups.

Reconquering the water: Evolution and systematics of South and Central American aquatic lizards (Gymnophthalmidae) - Sergio Marques‐Souza; Ivan Prates; Antoine Fouquet; Agustín Camacho; Philippe J. R. Kok; Pedro M. S. Nunes; Francisco Dal Vechio; Renato Sousa Recoder; Nathalia Mejia; Mauro Teixeira Junior; Cesar Barrio‐Amorós; José Cassimiro; et al. (Zoologica Scripta, 2018)
The Cercosaurini tribe stands out from other Gymnophthalmidae lizards for including several species with morphological adaptations to aquatic lifestyle (“Crocodile‐Like Morphology” – CLM ). Recent molecular phylogenies of Cercosaurini demonstrated the paraphyly of CLM species, implicitly suggesting that adaptations to the aquatic life evolved more than once. However, CLM species have remained poorly sampled, and a number of uncertainties persist, such as the monophyly of Neusticurus and the placement of Potamites apodemus within the tribe. Based on a more extensive molecular and morphological data set, we propose a phylogenetic hypothesis for Neusticurus and investigate, for the first time, the phylogenetic position of P . apodemus . We recovered a monophyletic Neusticurus clade; however, Neusticurus rudis as currently understood was recovered as paraphyletic, with two lineages that also show consistent morphological diagnosis; as a result, we resurrect and provide a taxonomic redescription of Neusticurus surinamensis Müller, . Moreover, because P. apodemus was recovered as sister to all other Echinosaura , we propose a new combination for this species ( Echinosaura apodema ). We also review the distribution of Neusticurus species, offering a comprehensive view of their biogeography. Lastly, our ancestral character reconstruction and dating analyses indicate that the CLM phenotype evolved four times independently during Cercosaurini′s evolutionary history. We hypothesize that the CLM phenotype and subsequent adaptation to aquatic life may be linked to the development of the Pebas Lake in western Amazonia during the Miocene.

Diversity of teiid lizards from Gran Chaco and Western Cerrado (Squamata: Teiidae) - Federico José Arias; Renato Recoder; Blanca Beatriz Álvarez; Eduardo Ethcepare; Matias Quipildor; Fernando Lobo; Miguel Trefaut Rodrigues (Zoologica Scripta, 2018)
The Gran Chaco dry forest ecoregion corresponds to the southern portion of the South America diagonal belt of open formations, being one of the most threatened subtropical woodland savannas in the world. The area is still poorly known biologically and has been suffering with impressively high forest cover loss in the last 10 years. Integrating morphological and molecular data, we detected and describe a cryptic new species of lizard genus Ameivula endemic from the eastern part of this ecoregion, the called Humid Chaco. Ameivula apipensis sp nov. is characterised by a whitish brown vertebral stripe in adults and juveniles, a lateral field without ocelli and with overlapping spot, presence of an interfrontoparietal scale in 46.2% of the specimens, 12–17 femoral pores, an hemipenis without lateral sac, five xiphisternal ribs, and by a combination of meristic features as confirmed by discriminant analysis. The new species was recovered sister to a clade from Western Cerrado in our analysis, the first phylogenetic hypothesis for the Ameivula and Glaucomastix genera based on 1977 base pairs of three mitochondrial (12S, 16S and cyt‐ b ) and one nuclear (c‐mos) genes, including all the recognised species at the moment. Maximum parsimony and Bayesian inference recovered the monophyly of Ameivula and Glaucomastix with strong support. Reinforcing previous studies, our results suggest the presence of additional cryptic species in Ameivula from the Western Cerrado.